Preparation of synbiotic fermented milk and evaluation of short-chain fatty acids production during storage study - Hati, Subrota; Mitali; Dr; Dr (Indian Journal of Dairy Science, 2024)
The fermented milk product was formulated using Lactobacillus cultures V3 and M5 with addition of corn-starch. Addition of 8% sugar was selected for the preparation of fermented milks based on various sensory attributes and overall acceptability. Optimized fermented milk (T) along with control where corn starch was replaced with skim milk powder (C) were analyzed for theirproximate composition, short chain fatty acids (SCFAs) production as well as changes in physico-chemical and sensory properties during storage at refrigerated temperature (5±2ºC) up to 28 days. The pH of fermented milks C and T had significant (P